Nouvel urbanisme, gentrification et mobilité quotidienne: leçons apprises des quartiers Plateau-Mont-Royal et Bois-Franc… - Barbonne, Rémy (La métropolisation et ses territoires, 2009)
Keywords: Gentrification; Navettage; Plateau Mont-Royal; Quartiers

L’action des promoteurs immobiliers dans le processus de gentrification du Sud-Ouest de Montréal - Gaudreau, Louis; Houle, Marc-André; Fauveaud, Gabriel (Recherches sociographiques, 2021)
Keywords: Arrondissements; Gentrification; Le Sud-Ouest; Logement

Gentrification, nouvel urbanisme et évolution de la mobilité quotidienne: vers un développement plus durable? Le cas du Plateau Mont-Royal (1998-2003) - Barbonne, Rémy (Recherches sociographiques, 2008)
Keywords: Gentrification; Navettage; Plateau Mont-Royal; Quartiers

Pour qui et à qui ce parc? Gentrification et appropriation de l’espace public dans l’arrondissement du Sud-Ouest de Montréal (Canada) - Bélanger, H. (Lien social et Politiques, 2010)
Keywords: Arrondissements; Gentrification; Le Sud-Ouest (arrondissement); Parcs; Places publiques

Sound, Deindustrialization, and Gentrification: The Changing Aural Landscape of Pointe-Saint-Charles - Luderowski, Muriel (Université Concordia, 2017)
Keywords: Chemins de fer; Grand Tronc; Pointe-Saint-Charles; Quartiers

Pauvreté et richesse dans la région montréalaise depuis l'après-guerre. Un paysage en mouvement - Séguin, Anne-Marie; Negron-Poblette, Paula; Apparicio, Philippe (Histoire de Montréal et de sa région, 2012)
Keywords: Gentrification; Pauvreté; Quartiers

Quels rôles pour les acteurs locaux dans les projets de revitalisation urbaine intégrée? Regard sur le projet Laurentien-Grenet à Montréal - Chabant, Ophélie (Université du Québec à Montréal, 2011)
Keywords: Cartierville; Gentrification; Quartiers

Poverty and Wealth in the Post-War Montreal Area: A Landscape in Motion - Séguin, Anne-Marie; Negron, Paula; Apparicio, Philippe (Montreal: The History of A North American City, 2018)
Keywords: Gentrification; Pauvreté; Quartiers

Le dispositif de revitalisation du quartier Sainte-Marie à Montréal - Trussart, Antoine (Université de Montréal, 2016)
Keywords: Gentrification; Quartiers; Sainte-Marie

Artères commerciales et relations de pouvoir : le cas de la Plaza Saint-Hubert à Montréal - Montfils-Ratelle, Charlotte (Université du Québec à Montréal, 2017)
Keywords: Gentrification; Rues; Saint-Hubert (rue)

Portrait croisé de l’évolution des déplacements des résidents et des personnes fréquentant l’arrondissement du Plateau-Mont-Royal (1998-2003): vers un développement plus durable? - Barbonne, Rémy (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2007)
Keywords: Arrondissements; Gentrification; Navettage; Plateau Mont-Royal (arrondissement)

Urban governance after urban renewal: The legacies of renewal and the logics of neighbourhood action in post-renewal Little Burgundy (1979 – 1995) - Goyette, Kiley (Université Concordia, 2017)
Keywords: Gentrification; Groupes populaires; Logement; Petite-Bourgogne; Quartiers

It Took a Tenants' Movement: Tenants and the Making of Habitations Jeanne-Mance (1959-1994) - Nettling, Pierson Christopher (Université Concordia, 2017)
Keywords: Drapeau, Jean; Gentrification; Groupes populaires; Logement; Maires; Quartiers; Saint-Jacques

From Balconville to Condoville, but Where Is Co-opville? Neighbourhood Activism in 1980s Pointe-Saint-Charles - Vickers, Simon (Labour / Le travail, 2018)
Keywords: Gentrification; Logement; Pointe-Saint-Charles; Quartiers; Rassemblement des citoyens et citoyennes de Montréal

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail